2021
DOI: 10.1186/s40168-021-01025-w
|View full text |Cite
|
Sign up to set email alerts
|

Protists as main indicators and determinants of plant performance

Abstract: Background Microbiomes play vital roles in plant health and performance, and the development of plant beneficial microbiomes can be steered by organic fertilizer inputs. Especially well-studied are fertilizer-induced changes on bacteria and fungi and how changes in these groups alter plant performance. However, impacts on protist communities, including their trophic interactions within the microbiome and consequences on plant performance remain largely unknown. Here, we tracked the entire micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(56 citation statements)
references
References 70 publications
7
49
0
Order By: Relevance
“…These ndings suggest that seasonal variations had an additional in uence on soil microorganisms concerning different plant species, which is consistent with other studies [17,19,20,[23][24][25][26][27][28]. As an example, unlike other studies in which potential biotic and abiotic environmental variables such as soil moisture [29,30], plant types [31], pH [12,13,29,32], litter chemistry [33], and fertilization/season-induced changes [34] contributed to shaping the composition of the protist structures, our PERMANOVA pro ling revealed that the key factor driving the protist community's structure was peroxidase (POD) (Fig. 3).…”
Section: Microbial Diversities Under Seasonal Variations and In Different Plantationssupporting
confidence: 91%
See 2 more Smart Citations
“…These ndings suggest that seasonal variations had an additional in uence on soil microorganisms concerning different plant species, which is consistent with other studies [17,19,20,[23][24][25][26][27][28]. As an example, unlike other studies in which potential biotic and abiotic environmental variables such as soil moisture [29,30], plant types [31], pH [12,13,29,32], litter chemistry [33], and fertilization/season-induced changes [34] contributed to shaping the composition of the protist structures, our PERMANOVA pro ling revealed that the key factor driving the protist community's structure was peroxidase (POD) (Fig. 3).…”
Section: Microbial Diversities Under Seasonal Variations and In Different Plantationssupporting
confidence: 91%
“…It has also been shown that protist communities create a dynamic hub in soil biota [34,84]. As bacteria and fungi are principal prey for phagotrophic and/or consumer protists as the dominant soil protist functional group in soils [12,13,77,85,86], biotic interactions within the soil microbiome can in uence protist diversity. The taxon-speci c manner of protist taxa was observed for their potential microbial prey by detecting different and/or speci c links between bacteria/fungi and protist lineages.…”
Section: Soil Microbial Co-occurrence Network Complexity Under Seasonal Successions and In Different Plantationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eukaryotic microbial communities of wild tomatoes were mainly composed of Opisthokonta, representing a broad range of eukaryotes, such as fungi and protists. Thereby, protists have been identified as key determinants for plant performance (Guo et al 2021). The phylum Stramenopiles, including the foliar oomycete Phytophthora infestans (causal agent of late blight disease in tomato), was rarely detectable in Canta and low abundant in Yangas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, we revealed that protists showed severe community fluctuations over time and due to fertilization, whereas communities of bacteria and fungi did not vary ( 15 ). We also revealed that bacterial and especially protistan communities and protistan species predict plant health unlike fungal communities ( 16 ). Therefore, microbiome studies should include multiple microbial groups, as otherwise misleading conclusions on bacterial community assembly, ecological patterns, or treatment effect sizes might be drawn.…”
Section: The Benefit Of Real Microbiome Studies Beyond the Focus On Bacterial Communitiesmentioning
confidence: 96%